Evaluation of performance and productivity of bitumen modified by three different additives - Erkus, Yunus; Kok, Baha Vural; Yilmaz, Mehmet (Elsevier Sci Ltd, 2020)
Modifying the bitumen in bituminous mixtures has become an inevitable solution against the increasing traffic volume and its damaging effects on the environment. Today, the mostly used additive in bitumen modification is styrene-butadienestyrene (SBS). However, due to the high cost of polymers, the waste vehicle tires, (CR) which contain rubber have been used alternatively as an additive. In addition, in order to solve the workability problem caused by the use of additives and also to contribute to the performance, Sasobit, which is a warm mixture additive has been used recently. In this study, the effects of using together the SBS, CR and Sasobit each of which has an ability to improve the different properties of the binder, were evaluated by softening point, viscosity, dynamic shear rheometer, and bending beam rheometer tests and also economically. As a result, it was determined that there are triple binder types in many combinations that are more efficient than the single use of SBS according to high temperature performance, but when the low temperature behavior is evaluated, the number of combinations decreases. In general, 6%CR + 2%SBS + 2% Sasobit modified binders were found to be more efficient than 6% SBS modification. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Bitumen modification; Crumb rubber; Styrene-butadiene-styrene; Sasobit; Rheological properties